AN ANALYSIS OF THE TEACHING SKILL OF ENGLISH STUDENTS IN MICROTEACHING COURSE AT MADAKO UNIVERSITY - Moh. Rafii Moh. Sata; Erna Erna (Jurnal Madako Education, 2020)
This study aims to determine what are the teaching skills that implemented by students in the microteaching course at the University of Madako Tolitoli. The type of this research is descriptive qualitative research that located in University of Madako Tolitoli. The data source consists of 10 students who had practiced microteaching class. Data collection techniques used interview and documentation. The result of this study shows that students majoring in English who had been followed the practice of microteaching implemented seven (7) teaching skills. They are opening skill, explaining skill, reinforcement, variation skill, questioning skill, class management skill, and closing and evaluating skill.Key words : teaching skill, microteaching